Integrative taxonomy of Cedrela (Meliaceae) leads to the recognition of a new species (C. tamaulipana) and the reinstatement of C. saxatilis - Sergio Ignacio Gallardo-Yobal; José Antonio Vázquez-García; Alma Rosa Villalobos-Arámbula; Teresa Terrazas; Hilda Palacios-Juárez; Dolores Marina Barragán-Reynaga; Martin Berrones; Alondra Salomé Ortega-Peña; Gerardo Hernández-Vera; Viacheslav Shalisko (PLoS ONE, 2025)
A new species of Cedrela (Meliaceae) is described and illustrated from recently discovered populations at Rancho del Cielo Biosphere Reserve, Tamaulipas, Mexico. The newly proposed species is morphologically close to C. monroana but differs from the latter in having a shorter habit, thinner terminal twigs, shorter space between leaf pairs along the rachis, shorter petiolules, smaller leaflets, smaller leaflet length-to-width ratio, less numerous secondary leaflet veins, shorter panicles, and yellowish green flowers, broadly obovoid to pyriform fruits, with valves opening at least at an angle of 20 degrees and brown mature capsules with prominent lenticels on valves. We provide a key to the Mexican species of Cedrela including the closely related C. monroana. Latitudinal differences also support the setting aside of the proposed species, which is the most septentrional among its close relatives within Cedrela. Bayesian inference and maximum likelihood analyses of nuclear (ITS) and chloroplast (accD, matK, rbcL, trnH-psbA, psbB-T-N, rpl16, rpoB, rpoC1, trnS-G) DNA sequences of 19 taxa of Cedrela plus 3 from related taxa, place the proposed new species within a clade including Mexican & Central American species. Based on morphological and phylogenetic evidence, we propose the reinstatement of C. saxatilis as a valid species, previously treated as a synonym of C. oaxacensis.